Sorrowful shores violence, ethnicity, and the end of the Ottoman Empire 1912-1923 - Gingeras, Ryan (Oxford studies in modern European history., 2009)
The Turkish Republic was formed out of immense bloodshed and carnage. In the years before the ascendancy of Mustafa Kemal Ataturk, towns and villages throughout Anatolia was wracked by intercommunal violence. 'Sorrowful Shores' presents a history of these bloody years of social and political transformation.